Appreciative inquiry in higher education a transformative force - Cockell, Jeanie, 1950- (Jossey-Bass higher and adult education series., 2012)
"Appreciative Inquiry (AI) is about making positive changes in the world so to incorporate it fully in higher education means it will have an exponential impact on the next generation of positive change makers in the world. This book puts the focus on AI in higher education. It provides unique stories and practical guidance on how AI can be applied in higher education and offers practitioners the AI concepts, frameworks and agendas. The book gives practitioners the theoretical concepts to ground their work and links AI to the positive psychology and strengths work that has influenced educational approaches in the first decade of the 21st century"--